PERGESERAN FUNGSI KESENIAN REOG CEMANDI DI DESA CEMANDI KECAMATAN SEDATI KABUPATEN SIDOARJO - ALDINOV GUSTIANI, NINDIA; YANUARTUTI, SETYO (APRON Jurnal Pemikiran Seni Pertunjukan, 2020)
Abstract Reog Cemandi is an authentic traditional art from Sidoarjo. Reog Cemandi was founded in 1922, telling about two teenagers who came from one of the boarding schools in the village of Cemandi, which Kyainya sent to fight against the Dutch armed with rattan wood. The function of Reog Cemandis performance during its establishment was as a spiritual means to ward off the danger that disturbed the residents of Cemandi Village. The development of the era has an impact on the shift in the function of the show, for this research aims to explain the form of presentation of Reog Cemandi in Cemandi Village; explain the shift in the function of Cemog Reog to the people of Cemandi Village and explain the factors that influence the shift of function of Cemog Reog. This research is a descriptive qualitative research with the object of Reog Cemandi art research in Cemandi Village. Data collection techniques are done by observation, interviews and documentation with taxonomic analysis techniques. The results showed that the form of Reog Cemandis presentation did not change in the presentation of the show both from the elements of motion, accompaniment, makeup, fashion, staging, and property. The shift of the Reog Cemandi performance function from the ritual function to the entertainment function. Shifting functions are influenced by internal (funding) and external (modernization) factors. Keywords: shift, function, art, Reog Cemandi